Delimitation of taxa in Amauroderma (Ganodermataceae, Polyporales) based in morphology and molecular phylogeny of Brazilian specimens - Gomes-Silva, Allyne Christina; Lima-Júnior, Nelson; Malosso, Elaine; Ryvarden, Leif; Gibertoni, Tatiana (Phytotaxa, 2015)
From 2007 to 2014, specimens of Amauroderma were collected mostly in North and Northeast Brazil. Additionally, material deposited in herbaria was reviewed. The analysed specimens represented 20 species, six of them new to science: Amauroderma albostipitatum, A. floriformum, A. laccatostipitatum, A. ovisporum, A. sessile and A. subsessile. Twelve species, three of them new, had their ITS and/or LSU region of the DNA sequenced. According to the results, Amauroderma is not monophyletic; A. partitum and A. schomburgkii are macro-morphologically variable species; the synonym of A. calcigenum with A. partitum is not supported, and the use of macro- and micro-morphological characters is a useful tool to delimit species of the genus.